A review of evidence-based interventions in Indian nutrition programs - Avula, Rasmi; Kadiyala, Suneetha; Singh, Kavita; Menon, Purnima (International Food Policy Research Institute, 2013)
The persistence of undernutrition in the face of India’s impressive economic growth continues to be of enormous concern. Though there are recognized essential inputs for child and maternal nutrition, less than 55 percent of mothers and children receive any of these inputs in India (Menon and Aguayo 2011). To better clarify the extent to which current nutrition programs in India incorporate essential inputs for nutrition, a team from POSHAN reviewed nutrition programs in India for the inclusion of such inputs and examined how these inputs are implemented and delivered.